A qualitative examination of health and health care utilization after the September 11th terror attacks among World Trade Center Health Registry enrollees - Welch Alice E; Caramanica Kimberly; Debchoudhury Indira; Pulizzi Allison; Farfel Mark R; Stellman Steven D; Cone James E (BMC, 2012)
Abstract Background Many individuals who have 9/11-related physical and mental health symptoms do not use or are unaware of 9/11-related health care services despite extensive education and outreach efforts by the World Trade Center (WTC) Health Registry (the Registry) and various other organizations. This study sought to evaluate Registry enrollees' perceptions of the relationship between physical and mental health outcomes and 9/11, as well as utilization of and barriers to 9/11-related health care services. Methods Six focus groups were conducted in January 2010 with diverse subgroups of enrollees, who were likely eligible for 9/11-related treatment services. The 48 participants were of differing race/ethnicities, ages, and boroughs of residence. Qualitative analysis of focus group transcripts was conducted using open coding and the identification of recurring themes. Results Participants described a variety of physical and mental symptoms and conditions, yet their knowledge and utilization of 9/11 health care services were low. Participants highlighted numerous barriers to accessing 9/11 services, including programmatic barriers (lack of program visibility and accessibility), personal barriers such as stigmatization and unfamiliarity with 9/11-related health problems and services, and a lack of referrals from their primary care providers. Moreover, many participants were reluctant to connect their symptoms to the events of 9/11 due to lack of knowledge, the amount of time that had elapsed since 9/11, and the attribution of current health symptoms to the aging process. Conclusions Knowledge of the barriers to 9/11-related health care has led to improvements in the Registry's ability to refer eligible enrollees to appropriate treatment programs. These findings highlight areas for consideration in the implementation of the new federal WTC Health Program, now funded under the James Zadroga 9/11 Health and Compensation Act (PL 111-347), which includes provisions for outreach and education.